1984
DOI: 10.1159/000124030
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Urotensin I/Corticotropin-Releasing Factor Immunoreactivity in Neurosecretory Neurons in the Caudal Spinal Cord of Fish

Abstract: Urotensin I (UI), one of the biologically active peptides isolated from the caudal spinal cord and urophysis of fish, exhibits a strong sequence homology with mammalian corticotropin-releasing factor (CRF). We have applied an antiserum to ovine CRF that cross-reacts completely with UI to sections taken from the caudal spinal cord and urophysis of the channel catfish (Ictalurus punctatus). Using the indirect immunofluorescence technique, the presence of striking Ul-like immunoreactivity was observed within disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The tissues were treated by 1 of 2 procedures: (1) the individual lobules were sectioned at 50 or 75 pm on a sliding microtome and processed by the peroxidase-antiperoxidase (PAP) method of Stemberger (1979) modified for free-floating sections as previously described (Cummings et al, 1983) or (2) the lobules were embedded together within a single block of brain paste in an orientation to permit sectioning of the lobules in the transverse or sagittal plane, and 10 pm sections of the frozen tissue block were cut in a cryostat. Slide mounted sections were hydrated with PBS and processed for the indirect immunofluorescence technique of Coons (1958) as modified and ureviouslv described for CRF (Onstott and Elde. 1984).…”
mentioning
confidence: 99%
“…The tissues were treated by 1 of 2 procedures: (1) the individual lobules were sectioned at 50 or 75 pm on a sliding microtome and processed by the peroxidase-antiperoxidase (PAP) method of Stemberger (1979) modified for free-floating sections as previously described (Cummings et al, 1983) or (2) the lobules were embedded together within a single block of brain paste in an orientation to permit sectioning of the lobules in the transverse or sagittal plane, and 10 pm sections of the frozen tissue block were cut in a cryostat. Slide mounted sections were hydrated with PBS and processed for the indirect immunofluorescence technique of Coons (1958) as modified and ureviouslv described for CRF (Onstott and Elde. 1984).…”
mentioning
confidence: 99%
“…Previous immunocytochemical studies have shown that most or all of the caudal neurosecretory cells in several teleost species display UI or corticotropin-releasing factor (CRF)/UI immunoreactivity (7,(9)(10)(11), while UII immunocytochemistry revealed the presence of a nonreactive population of neurosecretory neurons in the caudal neurosecretory system, which is variable in percentage among different species (7,12).…”
mentioning
confidence: 99%
“…Neurons producing UI were immunohistochemically localized by FISHER et al (1984) in the caudal neurosecretory system of the white sucker, Catostomus commersoni, using an antiserum to UI of the same species. Further, antisera to the corticotropin-releasing factor (CRF) and sauvagine were successfully used to localize a UI-like substance, since CRF and sauvagine have several amino acid sequences homologous with UI (CRF: LARSON et al, 1984;ONSTOTT and ELDE, 1984;BERN et al, 1985;OWADA et al, 1985b;YAMADA et al, 1985;sauvagine: RENDA et al, 1982). Neurons producing UII were also immunohistochemically located in several species of teleosts (LARSON et al, 1984;OWADA and KOBAYASHI, 1984;BERN et al, 1985;OWADA et al, 1985a;YAMADA et al, 1985) and in elasmobranchs (OWADA et al, 1985b).…”
Section: Discussionmentioning
confidence: 99%